E×B staircases and barrier permeability in magnetised plasmas. (17th November 2016) - Hornung, G.; Dif-Pradalier, G.; Clairet, F.; Sarazin, Y.; Sabot, R.; Hennequin, P.; Verdoolaege, G.
Abstract: In-depth experimental characterisation of spontaneous shear flow patterning into a so-called E × B staircase—named after its planetary analogue—is shown in magnetised plasma turbulence, using ultrafast-sweeping reflectometry in the Tore Supra tokamak. Staircase signatures are found in a large variety of L-mode plasma conditions. Sensitivity to the dominant source of free energy is highlighted for the first time. A connection between staircase shear layer permeability and deviation from gyro-Bohm confinement scaling is strongly suggested, opening new routes to understanding confinement in drift-wave turbulence.